PENERJEMAHAN RENCANA STRATEGI MENJADI PROGRAM KEGIATAN MENGGUNAKAN BALANCED SCORECARD UNTUK PENGUKURAN KINERJA DAN AKUNTABILITAS DINAS LALU LINTAS DAN ANGKUTAN JALAN - Wahyudi Wahyudi; Bambang Tjahjadi (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: The purpose of this study is intend to knowing the level of understanding of person who make initiative related to the strategic plan of Dinas Lalu Lintas dan Angkutan Jalan Provinsi Jawa Timur; also knowing the methods used in elaborating a strategic plan into initiative; c. Knowing the performance measurement has been using as expected; and provide inputregarding the efforts that need to be done in translating strategicplans.Methods: This study uses the Balanced Scorecard model as a strategic management system to translate the strategic plan into an activity program at the Road Traffic and Transportation Office of East Java Province.Results: The results of this research indicated that a Vision Statement Dinas Lalu Lintas dan Angkutan Jalan Provinsi JawaTimur can not provide a clear picture about the success rate to be achieved; b. Mission Statement Dinas Lalu Lintas dan Angkutan Jalan Provinsi Jawa Timur have not been able todemonstrate the importance of the existence of the Office; c.Formulation of document strategic plan Dinas Lalu Lintas dan Angkutan Jalan Provinsi Jawa Timur has not been in accordance with what is expected; d. Realization of the budget that are noteffective and not performance oriented; e. Targetperformance of Dinas Lalu Lintas dan Angkutan Jalan Provinsi Jawa Timur has not been measured or is shaped qualitative rather than quantitative; f. Unavailability of data used as the basis for determining the level of achievement of a initiative.Conclusion and suggestion: The vision and mission statement of Dinas Lalu Lintas dan Angkutan Jalan Provinsi Jawa Timur needs to be restructure and rearrangement objectives, Goals and Strategies Department